2011
DOI: 10.1080/08959285.2011.597473
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Measuring Faking Behavior

Abstract: This article reviews different methods of measuring the extent that faking has distorted responses to a personality test. Based on the idea that faking causes shifts in the means and construct relationships, a three-factor framework is proposed for classifying such measures based on the data required for computation and the effect of faking that the measure is intended to gauge. Advantages and disadvantages for each method are discussed along with recommendations for measuring faking in research and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 35 publications
(52 reference statements)
1
81
0
1
Order By: Relevance
“…Neben den praktischen Implikationen von Faking bedarf es aus wissenschaftlicher Sicht noch eines Erkenntnisgewinns zum Faking-Prozess (Burns & Christiansen, 2011;. Ist Faking ein Prozess, der reproduziert werden kann, oder ist dieser bei Zulassungsverfahren derart komplex, dass er es nicht werden kann?…”
Section: Die Vorliegende Studieunclassified
“…Neben den praktischen Implikationen von Faking bedarf es aus wissenschaftlicher Sicht noch eines Erkenntnisgewinns zum Faking-Prozess (Burns & Christiansen, 2011;. Ist Faking ein Prozess, der reproduziert werden kann, oder ist dieser bei Zulassungsverfahren derart komplex, dass er es nicht werden kann?…”
Section: Die Vorliegende Studieunclassified
“…However, these scales have been criticized for being correlated with personality traits and fakeable themselves (Burns & Christiansen, 2011;Ones et al, 1996). Thus, the inability of SDR scales to detect faking strongly contrasts their actual spread in personnel selection.…”
Section: Threats and Drawbacks Of Frequently Used Detection Methodsmentioning
confidence: 99%
“…Currently, a number of methods of measuring faking exist (for an overview, see Christiansen, 2011 and, used in research as well as in personnel selection. O'Connell and colleagues (2011) demonstrated that different detectors of faking result in different classifications of respondents.…”
Section: Threats and Drawbacks Of Frequently Used Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A difference score is by definition correlated with the components from which it is derived (Burns & Christiansen, 2011;Pedhazur & Schmelkin, 1991). Thus, if trait EI is highly correlated with a personality facet in the honest condition, then this shared variance between EI and the facet itself could be responsible for any relation found between EI and the difference score based on this facet.…”
Section: Statistical Analysesmentioning
confidence: 99%